PENYADARTAHUAN KONSERVASI HABITAT SATWA LIAR MELALUI MEDIA ANIMASI BERBASIS ANDROID UNTUK SISWA-SISWI SMP DI KAWASAN EKOSISTEM LEUSER, ACEH TIMUR - Armanda, Fahmy; Saumi, Fazrina; Aprilia Putri, Kartika; Yusman Persada, Andri; Endah Sari, Herlina Putri; Purnama Febri, Suri (Fakultas Ilmu Komputer, 2025)
The Leuser Ecosystem Area is an ecosystem area protected which contains a variety of biodiversity, most importantly endemic animals such as orangutans, Sumatran rhinos, Sumatran tigers and Sumatran elephants. Serbajadi District, East Aceh Regency is an area included in the Leuser Ecosystem area where cases of conflict between humans and wild animals often occur, such as damage to residents' plantations and agricultural areas by wild animals and even cases of death of wild animals and humans. This community service activity related to awareness of wildlife habitat conservation is carried out with the aim of providing an early understanding of the importance of understanding conservation of wild animal habitats from an early age through learning media with Android-based animation. The method used in this activity is Participatory Action Research. This activity was carried out in a participatory manner between the school as a partner, non-governmental organizations as sources of data on wildlife conflict cases, and the service team. Learning media in the form of Android-based animations is presented based on conditions occurring in society related to wildlife habitat conservation and solutions to problems that arise. The results of this activity are through Android-based animation media that is appropriate to the age level of students so that early awareness emerges within students of the importance of conservation of wild animal habitats as part of efforts to resolve frequent cases of conflict between wild animals and humans occurred in that area.